Union citizens' rights against their own Member State after Brexit. Issue 3 (June 2020) - Bernard, Nicolas
The treatment by the United Kingdom of Union citizens remaining on its territory after Brexit and conversely that of UK nationals by EU27 Member States on theirs has given rise to much discussion and analysis. By contrast, there has been comparatively little systematic and detailed exploration of the question of the impact of Brexit on the exercise of Union citizens' rights against their own Member State. It is an issue which is for the most part ignored in the current Withdrawal Agreement. The purpose of this article is to show that this blind spot opens up a potential gap in legal protection of the rights of Union citizens, which is likely to remain regardless of the outcome of the Brexit negotiations and whether a withdrawal agreement is concluded or not. The paper discusses the extent to which the adversarial nature of the withdrawal process has contributed to this failure to address this issue and the ways in which courts could step in to provide the legal protection that political processes were unable to deliver.